A phenotypic characterization of two isolates of a multidrug-resistant outbreak strain of mycobacterium tuberculosis with opposite epidemiological fitness - Bei, Jinlong; Bigi, María Mercedes; Lima, Analía; Zhang, Qi; Blanco, Federico Carlos; López, Beatriz; Yu, Ting; Wang, Zhilin; Dai, Zhangyan; Chen, Zhuang; Cataldi, Angel Adrian; Sasiain, María del Carmen; et al. (Hindawi, 2020)
Tuberculosis (TB) is an infectious disease, caused by Mycobacterium tuberculosis, primarily affecting the lungs. The M. tuberculosis strain of the Haarlem family named M was responsible for a large multidrug-resistant TB (MDR-TB) outbreak in Buenos Aires. This outbreak started in the early 1990s and in the mid 2000s still accounted for 29% of all MDR-TB cases in Argentina. By contrast, a clonal variant of strain M, named 410, has caused a single tuberculosis case since the onset of the outbreak. The molecular bases of the high epidemiological fitness of the M strain remain unclear. To assess its unique molecular properties, herein, we performed a comparative protein and lipid analysis of a representative clone of the M strain (Mp) and the nonprosperous M variant 410. We also evaluated their growth in low pH. The variant 410 had higher levels of latency proteins under standard conditions and delayed growth at low pH, suggesting that it is more sensitive to stress stimuli than Mp. Moreover, Mp showed higher levels of mycolic acids covalently attached to the cell wall and lower accumulation of free mycolic acids in the outer layer than the 410 strain. The low expression of latency proteins together with the reduced content of surface mycolic acids may facilitate Mp to evade the host immune responses.